2022
DOI: 10.3389/fmicb.2022.946631
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic profiles of Dermacentor tick pathogens from across Mongolia, using next generation sequencing

Abstract: Tick-borne diseases are a major public health concern in Mongolia. Nomadic pastoralists, which make up ~ 26% of Mongolia’s population, are at an increased risk of both tick bite exposure and economic loss associated with clinical disease in herds. This study sought to further characterize tick-borne pathogens present in Dermacentor ticks (n = 1,773) sampled in 2019 from 15 of Mongolia’s 21 aimags (provinces). The ticks were morphologically identified and sorted into 377 pools which were then screened using Nex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…According to our study, Rickettsia seroprevalence was higher in the western provinces than in the eastern provinces. Altantogtoh et al [ 44 ] previously reported that Rickettsia was more prevalent in tick pools in the western and eastern provinces of Mongolia than in those in the other provinces. This shows that there is considerable geographic variability in the ecology of Rickettsia spp.…”
Section: Discussionmentioning
confidence: 99%
“…According to our study, Rickettsia seroprevalence was higher in the western provinces than in the eastern provinces. Altantogtoh et al [ 44 ] previously reported that Rickettsia was more prevalent in tick pools in the western and eastern provinces of Mongolia than in those in the other provinces. This shows that there is considerable geographic variability in the ecology of Rickettsia spp.…”
Section: Discussionmentioning
confidence: 99%
“…Tick-borne viruses pose a significant health threat to human and animal populations. With the application of high-throughput sequencing technology, many novel tick-borne bacteria and viruses have been identified in various ticks around the world, including countries like Korea, Mongolia, Nigeria, and China ( Kamani et al., 2019 ; Altantogtokh et al., 2022 ; Lee et al., 2023 ; Yang et al., 2023 ). Researchers detected numerous arboviral viruses by next-generation sequencing (NGS) technology in 640 ticks collected in eight provinces in central and western China, including 13 novel viruses ( Yang et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%